Genetic Variation in Renal Expression of Folate Receptor 1 (Folr1) Gene Predisposes Spontaneously Hypertensive Rats to Metabolic Syndrome - Pravenec, Michal; Kožich, Viktor; Krijt, Jakub; Sokolová, Jitka; Zídek, Václav; Landa, Vladimír; Mlejnek, Petr; Šilhavý, Jan; Šimáková, Miroslava; Škop, Vojtěch; Trnovská, Jaroslava; Kazdová, Ludmila; et al. (Hypertension (Dallas, Tex., 2016)
Metabolism of homocysteine and other sulfur amino acids is closely associated with metabolism of folates. In this study, we analyzed the possible role of folates and sulfur amino acids in the development of features of the metabolic syndrome in the BXH/HXB recombinant inbred strains derived from the spontaneously hypertensive rat (SHR) and Brown Norway progenitors. We mapped a quantitative trait locus for cysteine concentrations to a region of chromosome 1 that contains a cis-acting expression quantitative trait locus regulating mRNA levels of folate receptor 1 (Folr1) in the kidney. Sequence analysis revealed a deletion variant in the Folr1 promoter region of the SHR. Transfection studies demonstrated that the SHR-promoter region of Folr1 is less effective in driving luciferase reporter gene expression than the Brown Norway promoter region of Folr1. Results in the SHR.BN-chr.1 congenic strain confirmed that the SHR variant in Folr1 cosegregates with markedly reduced renal expression of Folr1 and renal folate reabsorption, decreased serum levels of folate, increased serum levels of cysteine and homocysteine, increased adiposity, ectopic fat accumulation in liver and muscle, reduced muscle insulin sensitivity, and increased blood pressure. Transgenic rescue experiments performed by expressing a Folr1 transgene in the SHR ameliorated most of the metabolic disturbances. These findings are consistent with the hypothesis that inherited variation in the expression of Folr1 in the kidney influences the development of the metabolic syndrome and constitutes a previously unrecognized genetic mechanism that may contribute to increased risk for diabetes mellitus and cardiovascular disease.
Keywords: Genetic Predisposition to Disease; cysteine; blood pressure; Rats; Real-Time Polymerase Chain Reaction; krevní tlak; Metabolic Syndrome; Hypertension; Gene Expression Regulation; mužské pohlaví; potkani inbrední SHR; genetická variace; metabolic syndrome X; Folate Receptor 1; krysa rodu Rattus; RNA; kvantitativní polymerázová řetězová reakce; Genetic Variation; regulace genové exprese; Rats, Inbred BN; zvířata; metabolický syndrom; Blood Pressure; potkani inbrední BN; rats, inbred SHR; ledviny; hypertenze; folate receptor 1; folátový receptor 1; Kidney; genetická predispozice k nemoci; Rats, Inbred SHR; Male; Animals